AMBIGUITAS KEPUTUSAN ADMINISTRASI NEGARA : ANTARA DISKRESI DAN LEGALITAS - Yudit Bertha Rumbawer; Donny Eddy Sam Karauwan; Anthon Rumbruren (Program Studi Hukum Tata Negara, Institut Agama Islam Negeri Parepare, 2024)
The decision-making process in public administration requires a balance between discretion and legality. Discretion provides officials the freedom to make decisions based on their personal judgment. However, discretion also has the potential to be misused. This research was conducted to identify and analyze the balance between the freedom to act and legal compliance in the decision-making process of the Indonesian government. This study employs a descriptive qualitative approach. The results of the study indicate that discretion has the potential to increase flexibility and effectiveness in decision-making, but it also has the potential for misuse. Therefore, a proper balance between the use of discretion and the principle of legality is necessary. Recommendations include enhancing the awareness and ability of administrative officials to use discretion appropriately and transparently, and improving the quality of legislation by providing clearer and more detailed guidelines. As a result, the government can function better and achieve better national objectives.